Analysis of Power System Affected by Extreme Weather and Its Adaptive Strategy - Geng LU; Jing DENG; Yuhong WANG; Jing CAO; Yunfeng YUE (发电技术)
The impact of climate change on human society has attracted more and more attention, and the risk of power outage caused by a series of extreme weather is becoming more and more significant. In order to deal with climate change, especially extreme weather, human society needs to adopt two coping strategies of mitigation and adaptation. For the developing countries and small island countries, since climate change has already taken place, the climate problem will first be adaptation. In order to solve the problem of how the power system can fully adapt to climate change from all aspects, a power system development system adapted to climate change was established, and a construction method of power system development path covering extreme meteorological factors was proposed. On the basis of summarizing the impacts of various extreme weather on the power system, the vulnerability of power grid was evaluated. The overall strategy of adapting to extreme weather was studied, and the scheme of power system adapting to extreme weather events was proposed, namely planning-construction-emergency management-assessment (PCEA) disaster resistance system. In the planning stage, the study focused on the minimum power grid planning and built the minimum power grid backbone network without power outage. Based on the application examples in different stages of the scheme, it was verified that the PCEA system can make the power system better adapt to the extreme weather.